Features of vaccination for children with allergic diseases - A. V. Zhestkov; O. O. Pobezhimova; O. S. Sidorova (Аллергология и Иммунология в Педиатрии)
Immunity prevention is a branch of immunology, where they study and develop methods and methods for specific prophylaxis of infectious and non-infectious diseases using immunobiological drugs that affect the function of the immune system. Immunity prevention is aimed at creating active or passive immunity to the causative agent of an infectious disease in order to prevent a possible disease by forming the body's immunity to it.Children with various history of aggravating factors are at risk. To avoid post-vaccination complications, all activities related to immunization of such patients should be performed especially carefully. The inclusion of a child in a risk group should in no way be considered as a basis for non-immunization, since the diseases targeted by immunity prevention in such children are often very difficult and give an unfavorable outcome. You can’t consider them “withdrawn” from vaccination — in fact, they are included in the lists of vaccines subject to the probable duration of the vaccine and the necessary conditions. Children assigned to risk groups, before vaccination require additional examination, drawing up an individual immunization schedule and a series of measures to prevent post-vaccination complications. It should be borne in mind that the degree of risk of complications varies for different vaccines.The doctor’s work with children from risk groups consists of several stages. First, it is necessary to give a general assessment of the child’s health status before vaccination and identify specific risk factors for the development of post-vaccination complications. Taking into account the history and results of the examination, the child is assigned to a particular risk group and, having determined the admissibility of immunization, an individual vaccination schedule is made.To date, in the age of the Internet and the media, when anyone can pass off their opinions as scientifically proven facts, there are opponents of vaccination. Among them there are not a few parents of healthy children, and children with chronic diseases, in particular with such an allergic disease as atopic dermatitis.The objectives of this article are: Find scientifically proven facts of the need for vaccination of children with allergic To note the features of vaccination of children with allergic